(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents a methodology for explaining mathematical terms in an elementary and accessible manner. The approach focuses on simplifying complex mathematical concepts by using everyday language, visual aids, and relatable examples to enhance comprehension among learners at the elementary level. By breaking down terminology and emphasizing intuitive understanding, the methodology aims to foster a positive attitude towards mathematics and improve learners’ confidence. The article discusses practical strategies for educators to implement this methodology effectively in classroom settings.